VD_FINDINFO HC / 2013 / 667 vom 8. Oktober 2013 - VD Tribunal cantonal (2013)
EXPERTISE, FRAIS JUDICIAIRES | 242 al. 2 CPC, 2 al. 1 TFJC, 25 TFJC, 257 TFJC, 184 al. 3 CPC (CH), 319 let. b ch. 1 CPC (CH), 320 CPC (CH), 322 al. 1 CPC (CH), 404 al. 1 CPC (CH), 405 al. 1 CPC (CH)